The impact of donor and recipient common clinical and genetic variation on estimated glomerular filtration rate in a European renal transplant population - Stapleton, Caragh P. (American journal of transplantation, 2019)
Genetic variation across the human leukocyte antigen loci is known to influence renal-transplant outcome. However, the impact of genetic variation beyond the human leukocyte antigen loci is less clear. We tested the association of common genetic variation and clinical characteristics, from both the donor and recipient, with posttransplant eGFR at different time-points, out to 5 years posttransplantation. We conducted GWAS meta-analyses across 10 844 donors and recipients from five European ancestry cohorts. We also analyzed the impact of polygenic risk scores (PRS), calculated using genetic variants associated with nontransplant eGFR, on posttransplant eGFR. PRS calculated using the recipient genotype alone, as well as combined donor and recipient genotypes were significantly associated with eGFR at 1-year posttransplant. Thirty-two percent of the variability in eGFR at 1-year posttransplant was explained by our model containing clinical covariates (including weights for death/graft-failure), principal components and combined donor-recipient PRS, with 0.3% contributed by the PRS. No individual genetic variant was significantly associated with eGFR posttransplant in the GWAS. This is the first study to examine PRS, composed of variants that impact kidney function in the general population, in a posttransplant context. Despite PRS being a significant predictor of eGFR posttransplant, the effect size of common genetic factors is limited compared to clinical variables.
Gesehen am 17.02.2020
Received: 23 October 2018
UK and Ireland Renal Transplant Consortium investigators: Maria P. Hernandez‐Fuentes, King's College London, MRC Centre for Transplantation, London, UK, UCB Celltech, Slough, UK; Gerhard Opelz, University of Heidelberg, Transplantation Immunology, Heidelberg, Germany [und weitere]